Mutational Analysis of Plum Pox Potyvirus Polyprotein Processing By the NIa Protease in Escherichia Coli - García, Juan Antonio; Laín, Sonia; Cervera, María Teresa; Riechmann, Josí Luis; Martín, María Teresa (Journal of General Virology, 1990)
A binary Escherichia coli expression system has been used to study the pathway for proteolytic processing of the plum pox potyvirus (PPV) polyprotein. Trans cleavage at the carboxyl end of the cylindrical inclusion protein occurred, although with lower efficiency than that at the large nuclear inclusion protein-capsid protein junction. No trans cleavage at the carboxyl end of the small nuclear inclusion protein (NIa) was detected. The proteolytic activities at different cleavage sites of several deletion and point mutations of NIa protein have been analysed. The large ΔSX deletion and two different point mutations at His 239 abolished proteolytic activity at all sites. The effect of other mutations, particularly a Glu substitution for Asp 274, depended on the particular cleavage site analysed. The results obtained with the PPV NIa protein mutants were similar to those reported for comparable mutations in the tobacco etch virus 49K protease, despite differences in the sequences recognized for processing. No evident competitive inhibition of the proteolytic activity of PPV NIa protease by the presence of an excess of the different protease mutants could be demonstrated.